THERMODYNAMIC AND ENERGY-BASED ANALYSIS OF GEAR WEAR PROCESSES (Multidisciplinary Journal of Science and Technology, 2025)
This article presents an in-depth thermodynamic and energy-based analysis of gear wear processes. Wear is defined as a set of physicochemical transformations resulting from friction, which lead to surface deformation, microcracks, and heat generation. The study explores key thermodynamic criteria such as entropy production, energy dissipation, and the coefficient of friction. Through thermodynamic modeling, energy distribution, heat flow, and microstructural changes are identified. The transformation of frictional energy into various forms-such as heat, deformation, and acoustic losses-is described using mathematical models. Additionally, temperature distribution and heat absorption in the contact zone are evaluated based on Fourier’s heat conduction equation. The research findings highlight the effectiveness of thermodynamic approaches in the design of gear systems. These approaches are particularly relevant for agricultural machinery, especially in extending the service life of transmission systems in cotton harvesting machines and enhancing the efficiency of maintenance operations.